The enhancement of thermoelectric performance of p-type Li doped Mg2Ge0.4Sn0.6 by Si addition. (June 2019) - Yuan, Guocai; Han, Shaobo; Lei, Xiaobo; Hu, Jizhen; Liu, Weishu; Wang, Qi; Chen, Chen; Zhang, Qian; Zhang, Qinyong; Gu, Meng
Abstract: Mg2 (Ge, Sn) solid solutions are eco-friendly thermoelectric materials in moderate temperature (500–800 K) range. However, p-type Mg2 (Ge, Sn) solid solutions show poor thermoelectric performance compared to the n-type counterpart. In this work, the filtering of low energy holes and the blocking of thermal excited electrons in Mg1.92 Li0.08 Ge0.4 Sn0.6 by Si addition are demonstrated, which optimize the power factor by interface barrier and reduce the lattice thermal conductivity by nanoscale composition fluctuation. Finally, the power factor of ~1.85 × 10 −3 Wm −1  K −2 and the dimensionless figure of merit ZT ~0.75 are achieved in Li doped Mg2 Ge0.4 Sn0.6 with Si addition at 723 K. Graphical abstract: When the band gap of matrix (Eg1 ) is smaller than the band gap of second phase (Eg2 ), the interface barriers in panel (a) may filter the low-energy holes while allowing the high-energy holes in the valence band (VB) before bipolar effect. Above thermal excited temperature, the energy barriers in panel (b) can filter the low-energy holes and simultaneously block the thermal excited electrons in the conduction band (CB) to suppress bipolar effect. Eventually, the results indicate that the power factor obviously increased and the thermal conductivity significantly decreased by the filtering of the low-energy holes and the blocking of the thermal excited electrons.Unlabelled Image